Cost-effectiveness and budget impact of pembrolizumab+axitinib versus sunitinib in patients with advanced clear-cell renal cell carcinoma in the Netherlands - Xander, Nicolas S. H.; Fiets, W. Edward; Uyl-de Groot, Carin A. (Frontiers in Oncology, 2023)
The phase 3 clinical trial KEYNOTE-426 suggested a higher efficacy regarding overall survival (OS) and progression-free survival (PFS) of pembrolizumab+axitinib compared to sunitinib as a first-line treatment for patients with advanced renal cell carcinoma. In this analysis, the potential cost-effectiveness of this combination treatment versus sunitinib for patients with advanced clear-cell renal cell carcinoma (accRCC) was examined from the societal perspective in the Netherlands.Methods: For this analysis, a partitioned survival model was constructed. Clinical data were obtained from the published KEYNOTE-426 trial reports; data on costs and (dis-)utilities were derived from published literature. Costs outside of the healthcare sector included treatment-related travel, informal care and productivity loss. Next to a probabilistic scenario analysis, various scenario analyses were performed that aimed at survival extrapolation, different utility values, treatment duration and drug pricing, as well as restricting the cohort to patients with an intermediate or poor prognosis. Further, a budget impact analysis over three years was conducted, in which a sensitivity analysis concerning ranges in costs and the number of patients was applied. Moreover, a scenario concerning increasing market penetration of pembrolizumab+axitinib up to a market share of 80% in the third year was analyzed.The incremental cost-effectiveness ratio (ICER) of pembrolizumab+axitinib was estimated at €368,396/quality-adjusted life year (QALY) gained, with an incremental QALY gain of 0.55 over sunitinib. The probability of cost-effectiveness at a willingness-to-pay threshold of €80,000/QALY was estimated at 0%, a 50% probability was estimated at €340,000/QALY. Cost-effectiveness was not achieved in any of the applied scenarios. The budget impact over three years amounted to €417.3 million upon instantaneous and full replacement of sunitinib, and to €214.9 million with increasing market penetration. This is a provisional file, not the final typeset article Conclusion: Pembrolizumab+axitinib was not estimated to be cost-effective compared to sunitinib as a first-line treatment for patients with accRCC in the Netherlands from a societal perspective. In none of the analyzed scenarios, cost-effectiveness was achieved. However, price reductions and shorter treatment durations might lead to a more favorable ICER.